STRATEGI MEMPERPANJANG UMUR TEMPAT PENGOLAHAN AKHIR (TPA) SAMPAH DI INDONESIA - Adi Mulyanto (Jurnal Rekayasa Lingkungan)
The existence of Municipal Solid Waste (MSW) is not received by the community. The problem is MSWalways be generated by the activities of human being. All of the cities, especially in Java Island, facediffi culties to look for an area for dumping the MSW. The most effective strategy is the prolongation oflandfi ll site. The method applied is to build the small facility of MSW handling in small area such as RWs(administrative unit at the next-to-lowest level in city) or in the villages. The main product will be compostand other recyclable materials such as plastics, metals, and so forth. Therefore, maximum about 10% to20% of MSW will be discard in the landfi ll site. To realize the facility of MSW handling in the area, it needsseveral equipment to help for producing the good compost.Key words: MSW, composting process.